Posterior Only Vertebral Column Resection (PVCR) for Fixed Angular Kyphosis (FAK). Issue 1 (April 2016) - El-Sharkawi, Mohammad; Koptan, Wael; Elmorshidy, Essam; Tammam, Hamdy; Hasan, Khaled; El Miligui, Yaser
Introduction: VCR is the most suitable osteotomy for rigid angular kyphosis especially if the correction needed is high. The prospective cohort study assessed the efficacy of Posterior Vertebral Column Resection (PVCR) in management of Fixed Angular Kyphosis (FAK). Patients and Methods: Thirteen cases of FAK managed by PVCR in Assiut University Hospital and followed up for a mean of 20.31 (12–48) months. Seven cases (53.8%) were females and six cases were males, the mean age was 13.77 years. Eleven cases were congenital (84.6%) and two cases were post tuberculous. Five cases (38.5%) affected the thoracic region, six cases (46.2%) affected thoracolumbar region and two cases (15.4%) affected lumbar region. VAS, ODI, SRS-22, and neurology together with local kyphotic angle were compared pre, post and at last follow up visit. One case suffered progressive paraplegia. Results: Five osteotomies were at L1; four at D11, and one osteotomy at D10, D12, L2 and L3. The VAS improved from 6.57 ± 2.14 to 1.29 ± 0.75 ( p  = 0.001). The mean ODI improved from 56.22 ± 20.59 to 22.81 ± 11.33 ( p  = 0.001). Total SRS-22 score improved from 2.11 ± 0.60 to 3.35 ± 0.65 ( p  = 0.002). The mean local kyphotic angle improved from 65.38°±29.95 to 14.69°±19.78 ( p  = 0.001), the mean operative time was 465.38 ± 76.44 (320–600) minutes and the mean blood loss was 3323 ± 934.6 (1600–4500) cc. The preoperatively neurologically impaired case recovered completely. Four cases suffered complications (30%), one case suffered postoperative weakness of quadriceps which improved with physiotherapy, two cases suffered asymptomatic proximal junctional kyphosis and one case experienced pull out screws which was revised. Conclusion: PVCR seems to be highly effective tool for correction of fixed angular kyphosis avoiding the morbidity of anterior or combined approaches.